Arterial Stiffness, Inflammatory And Atherogenic Markers In Gestational Diabetes - Aziz, Salmi Ab (2011)
Gestational diabetes mellitus (GDM) is one of the common medical complications occurring during pregnancy, affecting approximately 1-18% of all pregnancies; depending on the population. Increased arterial stiffening has been demonstrated consistently in both Type 1 and Type 2 diabetes in a number of studies. Arterial stiffness has been shown to precede cardiovascular diseases. The assessment of arterial stiffness allows early detection of cardiovascular disease and may help in preventive strategies. Pulse wave velocity (PWV) and pulse wave analysis (PWA) are non invasive method used to assess arterial stiffness. Inflammatory and the atherogenic markers may influence vascular function and arterial stiffness. The objectives of this thesis were to determine whether gestational diabetes mellitus (GDM) is associated with increased arterial stiffness, inflammatory and atherogenic markers compared to age and gestational age matched controls. Inflammatory and atherogenic markers measured in this study include tumor necrosis factor alpha (TNF-α), high sensitivity C-reactive protein (hsCRP) and plasminogen activator inhibitor-1 (PAI-1) as a parameters.